Neutrophil-to-lymphocyte ratio and monocyte-to-lymphocyte ratio predict length of hospital stay in acute myocarditis. (14th October 2021) - Schmutzler, L; Mirna, M; Topf, A; Hoppe, U C; Lichtenauer, M
Abstract: Background: Neutrophil-to-lymphocyte ratio (NLR) and monocyte-to-lymphocyte ratio (MLR) are associated with the severity of various diseases, for example sepsis and coronary artery disease. So far, these ratios have not been described in patients diagnosed with myocarditis. The aim of this study was to demonstrate the relationship of NLR and MLR with the severity of acute myocarditis. Materials and methods: 224 consecutive patients with myocarditis were retrospectively enrolled in this study. Laboratory parameters and clinical data were extracted from hospital records and discharge letters. Results: Median NLR was 2.48 (IQR 1.51–4.71) and median MLR was 0.42 (IQR 0.29–0.58). NLR and MLR correlated with HF, CRP and leukocyte count. NLR further correlated with pBNP (rs= 0.390, p=0.037) and inversely with oxygen saturation (rs=−0.620, p=0.042), whereas MLR correlated inversely with LV systolic function (rs=−0.386, p=0.018). Both ratios correlated better with length of hospital stay (NLR: rs= 0.450, p=0.001, MLR: rs= 0.547, p<0.0001) than CRP, leukocyte count, troponin, CK or pBNP. In multiple linear regression analysis, a model with eGFR and MLR achieved the best predictive ability for length of stay (adj. R 2 = 0.61, p<0.0001). AUCs for the prediction of prolonged hospital stay (NLR= 0.79, MLR= 0.82), and optimal cut-offs therefor were calculated (NLR= 4.00 (sens.: 68%, spec.: 84%), MLR= 0.48 (sens.: 79%, spec.: 78%)). Patients who met the combined endpoint of in-hospital complications showed a higher NLR, however, this remained statistically insignificant (NLR: median 3.59 (IQR 1.60–10.13) vs. 2.49 (IQR 1.51–4.60), p=0.288). Conclusion: NLR and MLR correlated with the length of stay, as well as with several clinical and laboratory parameters in patients with myocarditis. Since white blood cell differentials are relatively easy and fast to perform, both ratios could facilitate further risk stratification in patients with acute myocarditis. FUNDunding Acknowledgement: Type of funding sources: None.